Using the Census Planning Database to Generate Differential Expected Yield Rates to Self-administered Mail Surveys. Issue 2 (May 2023) - Lewis, Taylor; McMichael, Joseph
Expected yield rates are essential to a survey's data collection plan, as they inform requisite sample sizes to meet the survey's objectives. Given an overall expected yield rate for a self-administered mail survey, this short take describes a simple method for using the Census Planning Database to assign differential yield rates to lower-level geographies within the study area.